2020
DOI: 10.1177/1745506520910911
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy complications in women of Russian, Somali, and Kurdish origin and women in the general population in Finland

Abstract: Objective: We compared the prevalence of gestational diabetes and hypertensive disorders in the most recent pregnancy among women of Russian, Somali, and Kurdish origin and women in the general population in Finland. Methods: The study groups were selected from population-based samples of 18- to 64-year-old women. The women were of Russian (n = 318), Somali (n = 583), and Kurdish (n = 373) origin or from the general population (n = 243), and had given birth in Finland between 2004 and 2014. The data were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…However, data are available on Somali immigrants. In 583 Somali women in Finland, the prevalence of GDM was 14.4% [ 63 ]. Data from immigrants have other biases; therefore, it is harder to extrapolate to the situation in Somalia.…”
Section: Gdm In Specific Arab Countriesmentioning
confidence: 99%
“…However, data are available on Somali immigrants. In 583 Somali women in Finland, the prevalence of GDM was 14.4% [ 63 ]. Data from immigrants have other biases; therefore, it is harder to extrapolate to the situation in Somalia.…”
Section: Gdm In Specific Arab Countriesmentioning
confidence: 99%
“…Pregnant women in Russia (1.7%), Kurdish (3.1%) and Somali (3.8%) had lower prevalence of PIH, compared to women in Finland (5.4%). 4 The PIH was observed to be the most common cause of maternal mortality in Ethiopia due to poor awareness. 1 Hypertension in pregnancy is expressed as a systolic blood pressure of 140 mmHg or greater and a diastolic blood pressure of 90 mmHg or greater.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women in Russia (1.7%), Kurdish (3.1%) and Somali (3.8%) had lower prevalence of PIH, compared to women in Finland (5.4%). 4 The PIH was observed to be the most common cause of maternal mortality in Ethiopia due to poor awareness. 1 …”
Section: Introductionmentioning
confidence: 99%
“…One previous study found that women of Kurdish origin had a higher risk of GDM compared to the general Finnish population. 20 The study was based on a relatively small sample of three migrant groups and could not be generalized to all women of migrant origin in Finland. 20 In recent years, the national prevalence of GDM increased from 11.5% in 2015 to 19% in 2019 in Finland.…”
Section: Introductionmentioning
confidence: 99%
“… 20 The study was based on a relatively small sample of three migrant groups and could not be generalized to all women of migrant origin in Finland. 20 In recent years, the national prevalence of GDM increased from 11.5% in 2015 to 19% in 2019 in Finland. 21 Most of the recent population growth in Finland has been due to migration flows and the fact that migrant origin women had a higher birth rate than Finnish origin women.…”
Section: Introductionmentioning
confidence: 99%